Acute complications after stroke and mortality - Laeka, Essay; Saeed, Hala; sosee, Heba (Latakia University Journal -Medical Sciences Series, 2018)
Introduction:Medical complications are common among patients with stroke. In our country, there is a limited information about the morbidity and mortality after an acute stroke in hospitalised patients. Aim:To study the frequency, type and timing of acute complications of stroke and the risk factors associated with these complications and the mortality rate. Materials and Methods:This is a prospective study, it was done at Al Assad and Tishreen University Hospitals, Lattakia, Syria, during the period between April 2016 –April 2017. 100 patientswith acute stroke were included and followed up with assessment of complications until discharge or death in the hospital. Results:61 patients(61%) experienced 1 or more complications. The most common complications were pneumonia in 19 patients (19%), urinary tract infection (UTI) in 12 patients (12%), seizures in 8 patients (8%), pressure sores in 6 patients (6%), depression in 6 patients (6%), constipation in 5 patients (5%). Complications developed more in older patients, and in patients with MCA involvement, with no important difference between males and females. No relation was found between risk factors of stroke and the development of complications after stroke. Most complications occurred early, the mean Length of stay (LOS) was 14 days, complications associated with longer LOS. Mortality rate in this study was 10% (10 patients), and 8 patients (80%) experienced 1 complication at least. The severity of stroke on admission was the most important risk factor for developing complications and associated with more mortality rate. Conclusion:Complications rate is 61% , they develop early, and associate with longer LOS. Mortality rate during hospitalization is 10% The severity of stroke on admission is the most important risk factor for developing complications and associated with more mortality rate. الاختلاطات الحادة في الحوادث الوعائية الدماغية ومعدل الوفيات. مقدمة: الاختلاطات المرضية شائعة عند مرضى النشبة, وهنالك محدودية في المعلومات المتعلقة بالمراضة والوفيات بعد النشبة الحادة عند المرضى المقبولين في المشفى في بلدنا. الهدف: دراسة تواتر, نمط, وتوقيت حدوث الاختلاطات الحادة في الحوادث الوعائية الدماغية وعوامل الخطر المرافقة لهذه الاختلاطات ومعدل الوفيات. المواد والطرق: دراسة مستقبلية, أجريت في مشفيي الأسد وتشرين الجامعيين في الفترة الممتدة من نيسان 2016 حتى نيسان 2017. شملت هذه الدراسة 100 مريض بتشخيص نشبة حادة, وتمت متابعتهم وتقييم حدوث الاختلاطات حتى التخريج من المشفى أو الوفاة ضمن المشفى. النتائج: 61 مريض (61%) عانى من اختلاط واحد على الأقل. كانت أكثر الاختلاطات شيوعاً: ذات الرئة عند 19 مريض (19%), الإنتان البولي عند 12 مريض (12%), الاختلاجات عند 8 مرضى (8%), قرحات الاضطجاع عند 6 مرضى (6%) , والإمساك عند 5 مرضى (5%). حدثت الاختلاطات أكثر عند المرضى الأكبر عمراً وعند إصابة الشريان المخي المتوسط(MCA), دون فرق في الحدوث بين الذكور والإناث. لم تشاهد علاقة بين عوامل الخطر لحدوث النشبة وتطور اختلاطات بعد النشبة. حدثت معظم الاختلاطات بشكلٍ مبكرٍ. بلغ متوسط مدة البقاء في المشفى(LOS) في مرضى هذه الدراسة 14 يوم, وترافقت الاختلاطات الحادة مع LOS أطول. بلغ معدل الوفيات في الفترة الحادة 10 مرضى (10%), و8 مرضى (80%) أظهروا وجود اختلاط واحد على الأقل. إن شدة النشبة عند القبول هي أهم عامل خطر لحدوث الاختلاطات عند مرضى النشبة, وتترافق مع حدوث الوفيات بشكل أكبر. الخلاصة: معدل حدوث الاختلاطات الحادة بعد النشبة 61%, وتحدث بشكل مبكر بعد الاستشفاء, وتترافق مع LOS أطول. معدل الوفيات خلال فترة الاستشفاء هو10%, شدة النشبة عند القبول هي عامل الخطر الأهم لحدوث الاختلاطات وتترافق مع معدل وفيات أعلى.